Systematic review of endoscopic-assisted surgical management for congenital nasolacrimal duct obstruction. (December 2020) - Trott, Skylar; Colgrove, Nicole; Westgate, Philip; Bush, Matthew; Iverson, Kenneth
Abstract: Objectives: Epiphora is a common presenting complaint in infants affecting up to 6% of infants in the United States. It is most frequently due to congenital anomalies of the nasolacrimal duct system, termed congenital nasolacrimal duct obstruction (CNLDO). Nasolacrimal duct probing is widely accepted as the primary surgical intervention in cases that fail conservative management. Recently, nasal endoscopy has been combined with traditional probing to improve success rates and outcomes. Several studies have been conducted, but the results have been inconclusive overall. The goal of this systematic review is to examine the existing literature on the role of nasal endoscopy during nasolacrimal duct probing and evaluate patient outcomes. Methods: A systematic search was performed in PubMed, MEDLINE, The Cochrane Library, ClinicalTrials.gov, LILAC, and EMBASE to identify peer-reviewed research. Eligible studies were those containing original peer-reviewed research in English addressing nasolacrimal duct probing for congenital nasolacrimal duct obstruction in conjunction with nasal endoscopy. Two investigators independently reviewed all articles and extracted data. Bias was assessed using the Cochrane Collaboration's tool, the Newcastle-Ottawa Assessment scale, and the NIH Quality Assessment scale. Results: A literature review ultimately yielded 11 articles that were selected and included in our analysis. Of the seven case series, the success rate was 92.5% for a total of 492 eyes. Of the four cohort/case-control studies, the success rate in conventional probings was 75.3% for a total of 293 eyes. In probings with nasal endoscopy, the success rate was 95.3% for 162 eyes. Overall, there was a high risk of bias and variation in data reporting amongst studies. Conclusion: Infants with congenital nasolacrimal duct obstruction that does not resolve with conservative treatment often require surgical intervention. Based on this systematic review of the current literature, nasal endoscopy is a useful adjunct for nasolacrimal duct probing.